PEMBERIAN PUPUK BOKASHI DAN LIMBAH CAIR PETERNAKAN SAPI PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Angga Dwi Farashi; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Oil palm production in the field is determined by the quality of seeds. To improve the quality of seeds is need for additional efforts of Bokashi fertilizer and liquid waste of cow farms.This study aimed to determine the effect of Bokashi fertilizer and liquid waste of cow farms and their combinations on the growth and development of oil palm seedling (ElaeisguineensisJacq.) in the main nursery. Next, to determine the best dose and concentration of Bokashi waste for seedling growth and development of oil palm (ElaeisguineensisJacq.) in the main nursery. This research was conducted at the experimental farm of the Agriculture Faculty, University of Riau in February to May 2015. This study was conducted using factorial CRD, the first factor is B1: Bokashi 2 tons/ha, B2: Bokashi 4 ton/ha and B3: Bokashi 6 tons/ha. The second factor is the liquid waste of cow farms that is U1: concentration of 300 ml/l, U2: concentration of 400 ml/l and U3: the concentration of 50 ml/l. Data were examined using analysis of variance and mean separation by DNMRT at 5%. The parametersthose  measured were seedling height increment, number of leaves, stem diameter increment, fresh weight and seedling dry weight. The results showed that the combination of Bokashi fertilizer and liquid waste of cow on the palm oil main nurseryare not significant on all parameters. The best result gained by the combination of Bokashi fertilizer and liquid waste of cow farms at the doses of 20 g/polybag and 500 ml/l of water.   Keyword : Bokashi fertilizer, liquid waste of cow farms, oil palm